Pengaruh Variasi Fraksi Volume Komposit Berpenguat Serat Pelepah Kelapa Sawit Terhadap Kekuatan Tarik - Daramawan, Tirta; Masdani, Masdani; Pranandita, Nanda (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The use of oil palm fronds is rarely used in the world of research. Oil palm fronds are only used in animal feed such as goats and cows, but in this study, oil palm fronds are used to make composite materials. Composites are a combination of reinforcement and binder. The reinforcement uses oil palm frond fiber while the binder uses resin. In this tensile test to determine the effect of the volume fraction of oil palm frond fiber with a volume fraction of 35%, 40%, and 45% while soaking in 5% NaOH for 2 hours. The results showed a tensile strength of 35% of 30.7 MPa, 40% of 38.8 MPa and 45% of 42.5 MPa. So the highest tensile strength is in the volume fraction of 45% and the lowest tensile strength is in the volume fraction of 35%.